1999
DOI: 10.1159/000054406
|View full text |Cite
|
Sign up to set email alerts
|

Hyporesponsiveness of the Pituitary to CRH during Slow Wave Sleep Is Not Mimicked by Systemic GHRH

Abstract: During slow wave sleep (SWS) pituitary responsiveness to CRH is reduced. Since GHRH is involved in the promotion of SWS in humans and rats, it was examined whether the blunted CRH-induced ACTH and cortisol release during SWS could be mimicked by systemic GHRH. Young healthy men (n = 7) participated in 4 sleep-endocrine protocols: (A) lights off at 23.00 h, intravenous injection of 50 µg CRH during the first SWS period; (B) lights off at 01.00 h, injection of 100 µg GHRH at 23.00 h, followed by 50 µg CRH at 23.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
1
8
0
8
Order By: Relevance
“…Subsequently, he had a large meal (Weikel et al, 2003). This observation fits with various studies from our laboratory and others showing that repetitive (Steiger and Holsboer, 1997;Weikel et al, 2003) and single (Kerkhofs et al, 1993;Antonijevic et al, 1999a) i.v. bolus injections of neuropeptides modulate human behavior, and in the latter experiments, modulate sleep.…”
Section: Introductionsupporting
confidence: 89%
“…Subsequently, he had a large meal (Weikel et al, 2003). This observation fits with various studies from our laboratory and others showing that repetitive (Steiger and Holsboer, 1997;Weikel et al, 2003) and single (Kerkhofs et al, 1993;Antonijevic et al, 1999a) i.v. bolus injections of neuropeptides modulate human behavior, and in the latter experiments, modulate sleep.…”
Section: Introductionsupporting
confidence: 89%
“…This could point to the importance of this frequency range as a state marker for depression in general. Interestingly, the EEG power in this frequency range is increased by CRH administration in healthy subjects (Antonijevic et al, 1999b) and rats (Ehlers et al, 1986), supporting an involvement of this peptide in the sleep-EEG changes observed in the course of antidepressant treatment and further pointing to its importance in the pathophysiology of depression (Holsboer, 1999). Earlier studies examining if specific sleep-EEG changes under psychopharmacological treatment are linked to clinical response failed to do so (Mendlewicz et al, 1991;Heiligenstein et al, 1994).…”
Section: Discussionmentioning
confidence: 75%
“…bolus of CRH in young healthy men. 52 Conversely, in sleep-deprived healthy humans, CRH induces higher increases in NREMS if given during the recovery night compared to placebo. 23 The responsiveness of sleep EEG to CRH appears to increase during ageing, since sleep disruption…”
Section: Corticotropin-releasing Hormone (Crh)mentioning
confidence: 99%